Physiological importance and role of Mg2+ in improving bacterial resistance to cesium - Ishida, Yoshiki; Zhang, Chongkai; Satoh, Katsuya; Ito, Masahiro (Frontiers in Microbiology, 2023)
Cesium (Cs) is an alkali metal with radioactive isotopes such as 137Cs and 134Cs. 137Cs, a product of uranium fission, has garnered attention as a radioactive contaminant. Radioactive contamination remediation using microorganisms has been the focus of numerous studies. We investigated the mechanism underlying Cs+ resistance in Microbacterium sp. TS-1 and other representative microorganisms, including Bacillus subtilis. The addition of Mg2+ effectively improved Cs+ resistance of these microorganisms. When exposed to high concentrations of Cs+, the ribosomes of Cs+-sensitive mutants of TS-1 collapsed. Growth inhibition of B. subtilis in a high-concentration Cs+ environment was because of drastic decrease in the intracellular potassium ion concentration and not the destabilization of the ribosomal complex. This is the first study demonstrating that the toxic effect of Cs+ on bacterial cells differs based on the presence of a Cs+ efflux mechanism. These results will aid in utilizing high-concentration Cs+-resistant microorganisms for radioactive contamination remediation in the future.